Moderate-to-vigorous physical activity of HFrEF patients is strongly associated with age, but not with functional capacity (6MWT), ejection fraction, NYHA, NT-proBNP, sex or BMI. (11th May 2022) - Siranec, M; Vetrovsky, T; Parenica, J; Miklikova, M; Pelouch, R; Precek, J; Vesely, J; Griva, M; Linhart, A; Belohlavek, J
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Czech Health Research Council of the Ministry of Health of the Czech Republic Introduction: Patients with heart failure with reduced ejection fraction (HFrEF) commonly have impaired functional capacity and exercise intolerance which negatively affect their daily living activities and quality of life. Patients' level of moderate-to-vigorous physical activity (MVPA) remains low. A popular, easily incorporated into everyday life activity is walking, which at a pace of 5 km/h can be considered moderate intensity physical activity. We explored whether the level of MVPA in HFrEF patients is associated with certain demographic and clinical parameters. Methods: We analysed baseline values of HFrEF patients recruited in a multicentre randomised controlled trial of a six-month walking intervention (WATCHFUL trial, ClinicalTrials.gov identifier: NCT03041610). Their physical activity was objectively measured over seven days using accelerometer ActiGraph wGT3X-BT worn on the waist. Weekly minutes of MVPA were calculated using Freedson (1998) algorithm. The association between minutes of MVPA and sex, age, body mass index (BMI), HF symptoms (NYHA class), left ventricular ejection fraction (LVEF), serum levels of NT-proBNP, and distance walked in a six-minute walk test (6MWT) was explored in a series of univariate and multivariate linear regression models. Results: One hundred twenty-two patients were included in the analysis (31 females and 81 males, age 63.2±11.7 years, BMI 30.1±5.4, NYHA class II/III: 99/13, LVEF 30.5±7.0%, NT-proBNP 1169±1888 ng/L, 6MWT 365±61 m). They accumulated 33.8±40.3 min/week of MVPA. The weekly minutes of MVPA were negatively associated with patients' age: being one year older was associated with 1.8 min (SE 0.3) less MVPA (p < 0.001). Neither sex, BMI, NYHA Class, distance walked in 6MWT, nor serum levels of NT-proBNP were associated with weekly minutes of MVPA. Conclusion: Our results show that moderate-to-vigorous physical activity of HFrEF patients was strongly associated only with age. Surprisingly, commonly used prognostic markers of heart failure such as ejection fraction, NYHA, NT-proBNP, and functional capacity (6MWT) did not show significant. Neither did sex nor BMI. Exercise rehabilitation and increased physical activity improve functional capacity and should be regularly recommended, and even emphasised with age.